2020
DOI: 10.15294/maj.v9i1.36879
|View full text |Cite
|
Sign up to set email alerts
|

Investment Training Moderates the Effect of Financial Literacy, Return and Risk on Investment Interest in Capital Markets

Abstract: This study aims to analyze the effect of financial literacy, return and risk on investment interests in the capital market members of Forum KSPM Kota Semarang with investment research as a moderating variable. This research uses structural equation model analysis with WarpPLS 6.0 to evaluate the relationship between variables and the effect of moderation on investor investment training with financial literacy, return, risk, and investment interest by conducting a survey of 113 respondents who were successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…The lower the nominal capital that is set, the lower the interest in investment will increase. In contrast to the results of research conducted by Fadli & Wijayanto, (2020), who examined the effect of minimum capital, returns, and risks and motivation on students' interest in investing in the capital market, where the results of his study concluded that minimum capital had no effect on investment intentions.…”
Section: The Effect Of Minimum Capital On Investment Interest In the ...mentioning
confidence: 60%
“…The lower the nominal capital that is set, the lower the interest in investment will increase. In contrast to the results of research conducted by Fadli & Wijayanto, (2020), who examined the effect of minimum capital, returns, and risks and motivation on students' interest in investing in the capital market, where the results of his study concluded that minimum capital had no effect on investment intentions.…”
Section: The Effect Of Minimum Capital On Investment Interest In the ...mentioning
confidence: 60%
“…Pada penelitian sebelumnya terkait pengaruh literasi keuangan terhadap investasi yang dilakukan oleh Faidah (2019) dan Fadli & Wijayanto (2020) masing-masing dalam penelitiannya menyatakan bahwa literasi keuangan berpengaruh pada minat investasi. Menurut Fadli & Wijayanto (2020) literasi keuangan seseorang dapat mempengaruhi minatnya dalam pengelolaan keuangan dan akan memikirkan tentang masa depan salah satunya adalah investasi.…”
Section: Pendahuluanunclassified
“…Interest is described as a motivational force that causes a person to be attracted to an object or other stimulus [14]. Based on Rizaldy et al [15] in the absence of coercion, interest can be defined as "a feeling that appears as a feeling of liking or being attracted to something". Interests may also develop for other reasons, such as personal or social considerations.…”
Section: Investment Interestmentioning
confidence: 99%
“…There are several previous studies which state that financial literacy affects students' interest in investing. In research conducted by [14], [15], [16], [17], [18], [37], [38], [39], [40], [41], demonstrates that college students who take financial literacy seriously are more likely to become investors. The following hypothesis may be drawn from the information presented above: H3: Financial literacy has an effect student investment interest.…”
Section: The Effect Of Financial Literacy (X3) On Student Investment ...mentioning
confidence: 99%